Bacterial aggregating activity in human saliva: comparisons of bacterial species and strains. - Malamud, D (1981)
Using a quantitative assay to measure saliva-mediated bacterial aggregating activity, we have surveyed 20 streptococcal strains with saliva samples obtained from a large population study. Individual saliva samples demonstrated characteristic levels of aggregating activity for Streptococcus sanguis M5. In general, high activity for this strain was associated with high activity for other strains of S. sanguis. Streptococcus mitis, and Streptococcus salivarius. The population distribution of aggregating activity for Streptococcus mutans, however, was different.